IPB University's Policy of Biodiversity’s Innovation for Eco-Edutourism - Arif Satria; Aceng Hidayat; Abdul Haris Abdul Haris (Journal of Sustainability Perspectives, 2021)
IPB University has declared as a Biodiversity Campus since 2011. This declaration was carried out considering the high biodiversity at the IPB University Campus. One of the causes of the high campus biodiversity is the uniqueness of the campus landscape and the maintained proportion between the built and open-green areas. The existence of lakes, forests, arboretums, plantations, and three rivers that cross the campus area has contributed to the high diversity of habitats and consequently to the biodiversity. At least 22 species of mammals, 99 species of birds, 12 species of amphibians, 38 species of reptiles, 128 species of butterflies, 173 species of woody-plants, 40 species of bamboos and 127 species of medicinal plats have been recorded inhabiting the 257 ha of the campus area. The biodiversity has significant role as objects for research of the students, lecturers, researchers as well as for tourism such as for bird watching, picture hunting, outbond and other recreational activities. Therefore the campus functions for education and for tourism, thus ecoedutourism for academic community as well as community around the campus. To maintain the biodiversity, IPB University issued several policy innovations. The first policy innovation is monitoring of population and distribution of biodiversity on a regular basis. Second, habitat management for biodiversity. Third, on-site and offsite socialization to campus and offcampus communities. Fourth, conserving the habitats of the flora and fauna. Fifth, rare tree planting. Sixth, the movement to plant fruit trees by each faculty. Seventh, conservation of biopharmaceutical medicinal plants. Eighth, building a garden for food sovereignty. Ninth, conducting research on campus biodiversity. All of these policies involve the academic community, experts, alumni and the community around the campus.